Transparent optical packet switching network architecture and demonstrators in the KEOPS project. - Gambini, P.
This paper reviews the work carried out in the ACTS KEOPS (Keys to Optical Packet Switching) project, describing the results obtained to date. The main objective of the project is the definition, development, and assessment of optical packet switching and routing networks, capable of providing transparency to the payload bit rate, using optical packets of fixed duration and low bit rate headers in order to enable easier processing at the network/node interfaces. The feasibility of the KEOPS concept is assessed by modeling, laboratory experiments, and testbed implementation of optical packet switching nodes and network/node interfacing blocks, including a fully equipped demonstrator. The demonstration relies on advanced optoelectronic components, developed within the project, which are described
Keywords: ACTS; KEOPS project; Keys to Optical Packet Switching; Fixed duration header; Laboratory experiments; Low bit rate header; Modeling; Network architecture; Network demonstrators; Network/node interfaces; Network/node interfacing blocks; Optical packet switching nodes; Optical routing networks; Optoelectronic components; Payload bit rate; Photonic packet switched networks; Synchronisation; Testbed implementation; Transparent optical packet switching